2017
DOI: 10.1016/j.ekir.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Protein and Energy Intakes With Protein-Energy Wasting Syndrome in Hemodialysis Patients

Abstract: IntroductionThe associations of dietary protein and/or energy intakes with protein or energy wasting in patients on maintenance hemodialysis are controversial. We examined these in the Hemodialysis (HEMO) Study.MethodsIn 1487 participants in the HEMO Study, baseline dietary protein intake (grams per kilogram per day) and dietary energy intake (kilocalories per kilograms per day) were related to the presence of the protein-energy wasting (PEW) syndrome at month 12 (defined as the presence of at least 1 criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In this presented study, respondents consuming less protein were simultaneously characterized by a lower intake of energy and most other nutrients. Similarly, in other research, CKD patients in highest baseline DPI and DEI quartiles had 4.11-fold (95% confidence interval: 2.79-6.05) higher odds of having protein energy wasting syndrome at month 12 [21]. These similarities may happen as a result of patients limiting the quantity of all consumed foods in an attempt to limit the level of protein in the diet.…”
Section: Discussionmentioning
confidence: 53%
“…In this presented study, respondents consuming less protein were simultaneously characterized by a lower intake of energy and most other nutrients. Similarly, in other research, CKD patients in highest baseline DPI and DEI quartiles had 4.11-fold (95% confidence interval: 2.79-6.05) higher odds of having protein energy wasting syndrome at month 12 [21]. These similarities may happen as a result of patients limiting the quantity of all consumed foods in an attempt to limit the level of protein in the diet.…”
Section: Discussionmentioning
confidence: 53%
“…In a study comparing dietary and nutrition status measures in HD patients by time on dialysis, investigators found increased energy and protein intake over time despite deteriorated measures of somatic protein [45]. Consistent with this, a prospective study unexpectedly identified a direct association between dietary protein and energy intake at baseline and PEW prevalence at 12 months, prompting the investigators to recommend excluding dietary measures from the definition of PEW [46].…”
Section: Discussionmentioning
confidence: 55%
“…31 Despite these established recommendations, the results of a recent study by Beddhuet al are worthy of comment. 44 In a retrospective analysis of the Hemodialysis (HEMO) study they examined the relationships of baseline dietary protein intake (DPI) and dietary energy intake (DEI) with the PEW syndrome at month 12 using the quartiles of these variables at baseline. Interestingly, those patients in the highest quartile of DPI or DEI had a higher risk of the PEW syndrome.…”
Section: Pe W/c Ache Xia Pre Venti On In Ck Dmentioning
confidence: 99%